การใช้คำถามปลายเปิดในการสอนคณิตศาสตร์ USING OPEN-ENDED QUESTION IN TEACHING MATHEMATICS - แก้วอ่ำ ระพีพัฒน์ (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2016)
บทคัดย่อ ในการจัดการเรียนการสอนคณิตศาสตร์ การใช้คำถามในชั้นเรียนมีส่วนสำคัญอย่างมาก เพราะคำถามที่ดีจะกระตุ้นความสนใจของนักเรียนให้กล้าคิด กล้าแสดงออก คำถามปลายเปิดเป็นคำถามที่เปิดโอกาสให้มีคำตอบได้หลากหลายมากกกว่า 1 คำตอบ และดึงเอาแนวคิดที่แตกต่างของนักเรียนออกมา ทำให้นักเรียนสามารถแสดงความคิดได้อย่างอิสระ พัฒนาทักษะการคิด การแก้ปัญหา การให้เหตุผล และเน้นให้นักเรียนได้สื่อสาร สื่อถึงแนวความคิด ทำให้ครูเข้าใจความคิดของนักเรียน และทำให้เกิดบรรยากาศในการเรียนรู้แลกเปลี่ยนความคิดเห็นซึ่งกันและกัน และทำให้การเรียนการสอนเป็นไปอย่างมีประสิทธิภาพ บทความนี้นำเสนอการใช้คำถามปลายเปิดในการสอนคณิตศาสตร์ โดยมีรายละเอียดเกี่ยวกับลักษณะของคำถามปลายเปิด ทำไมต้องใช้คำถามปลายเปิด การสร้างคำถามปลายเปิด และตัวอย่างการปรับเปลี่ยนคำถามปลายปิดให้เป็นคำถามปลายเปิดในการสอนคณิตศาสตร์ Abstract Using questions in learning management in mathematics is extremely important good questions will stimulate students’ interest of to be assertive. The open-ended questions give students’ a chance to have variety answers which is more than only one answer and get the different concepts of ideas from the students. Therefor; the students could express their ideas freely develop their thinking skill, problem solving skill and reasoning skill as well as emphasize students on communication which conveys their ideas. Teachers will understand students thought in learning atmosphere where teachers and students can share their thought. This let the learning become effective. This paper presented using open-ended question in teaching mathematics, the details of which included characteristics of open-ended question why use open-ended question creating open-ended question and examples revised closed-ended questions are open-ended question